1993
DOI: 10.1002/hep.1840180114
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of normal and injured human liver regeneration after hepatectomy as assessed on the basis of computed tomography and liver function

Abstract: We compared liver volume and function kinetics after partial hepatectomy according to extent of resection and severity of coexisting liver disease in 57 adults with uneventful postoperative courses. Liver volume and massiveness of resection, or resection rate, were estimated on computed tomography. Patients were categorized into three groups on the basis of reaction rate: small (< 30%), medium (30%-50%) and large (> 50%). The regenerative patterns of normal livers in the medium and large groups consisted of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
115
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(126 citation statements)
references
References 18 publications
8
115
3
Order By: Relevance
“…Although it is well established that partial hepatectomy induces hypertrophy of the liver,[19-28] we found that partial hepatectomy of the FLR prior to PVE did not accelerate but rather impaired hypertrophy induced by PVE. This finding can be explained by 3 separate findings previously reported in the literature.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Although it is well established that partial hepatectomy induces hypertrophy of the liver,[19-28] we found that partial hepatectomy of the FLR prior to PVE did not accelerate but rather impaired hypertrophy induced by PVE. This finding can be explained by 3 separate findings previously reported in the literature.…”
Section: Discussioncontrasting
confidence: 81%
“…First, the effect of liver regeneration after hepatectomy is to revert the volume to the preoperative status, not to surpass the original volume. [19, 21, 23, 24] Second, complete regeneration of the resected liver generally takes 6 months [23, 28] to 1 year [25, 26] after surgery. Finally, a positive correlation has been found between resection volume and hypertrophy of the liver after hepatectomy, and a small resection does not trigger liver hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…27, 28 Other possible factors include chronic liver disease, 22, 29 diabetes, 30, 31 and chemotherapy, 32, 33 although these have not been consistently shown to be significant. 3436 More recent studies have not found chemotherapy to be associated with poor growth. 11, 27, 3739 …”
Section: Discussionmentioning
confidence: 99%
“…For nearly 30 years, CT volumetry has been used to study liver regeneration after major hepatic resection for liver donation and resection of malignant tumors (30-32). The rate of hepatic regeneration in normal livers is thought to start with a rapid increase in the first two weeks after surgery, followed by a decrease (possibly due to reduction in edema), and a slow and steady increase (32, 33), and is influenced by liver function (30, 33, 34) and obesity (35). Whether the extent of resection correlates with regeneration rate is debatable (27, 33).…”
Section: Discussionmentioning
confidence: 99%